Preparation method of cellulose nanocrystal with excellent dispersibility

By controlling the mass ratio of DMF to CNC and using cosolvent strategies of DMF and water, the problem of poor aggregation and redispersion of cellulose nanocrystals after drying is solved, and the preparation of chiral structural color materials with excellent optical properties is achieved.

CN119912591AActive Publication Date: 2025-05-02SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510111074.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-05-02
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Cellulose nanocrystals (CNCs) are prone to aggregation after drying, resulting in poor redispersion and prone to problems of bacterial growth and strong hygroscopicity during storage.

Method used

By controlling the mass ratio of DMF to CNC, the dispersion of CNC suspension particles is improved, and the cosolvent strategy of DMF and water is used to reduce hydrogen bonds between CNCs and improve the colloidal stability of the redispersed suspension.

Benefits of technology

The redispersion effect of CNC particles is significantly improved, the optical properties of the film are improved, and the apparent color of the film is uniform and the surface is flat, and the problems of bacterial growth and strong hygroscopicity are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912591A_ABST
    Figure CN119912591A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of cellulose nanocrystals with excellent dispersibility, and belongs to the technical field of nanocellulose dispers.The method comprises the steps that CNC suspension liquid and a polar organic solvent are stirred and mixed to be uniform, and then ultrasonic treatment is conducted to obtain composite suspension liquid; performing evaporation-induced self-assembly on the composite suspension to obtain the cellulose nanocrystal-based composite iridescent film; diluting the cellulose nanocrystal-based composite iridescent film to form a re-dispersed composite suspension, freeze-drying the composite suspension, and then re-dispersing the dried product to obtain the cellulose nanocrystal with excellent dispersity; according to the method, an organic solvent such as N, N-dimethylformamide is introduced, so that the problems that bacteria are easy to grow and the hygroscopicity is strong in the storage process of CNC are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the dispersion technology of nanocellulose and the optical performance field of chiral photonic crystal films thereof, and specifically to a method for preparing cellulose nanocrystals with excellent dispersibility. Background Art

[0002] Cellulose nanocrystals (CNC) are a type of nanoscale cellulose extracted from natural fibers. They are usually rod-shaped, spherical, disc-shaped, etc. They not only have the characteristics of nanoparticles, but also have some unique strength and optical properties. The preparation of CNC-based chiral materials with excellent optical properties has certain challenges, which also makes it have broad application prospects.

[0003] CNC particles can generally be divided into two types: solid powder and suspension. However, its solid powder form has disadvantages such as low thermal stability and poor dispersibility. In order to improve its dispersibility, it can usually be modified by simple mixing of ionic liquids to obtain high-performance CNC powder. At present, the solid content concentration of well-dispersed unmodified CNC suspension is low, resulting in high storage and transportation costs of CNC, and it is difficult to prevent the growth of bacteria and fungi in the suspension. In addition, CNC requires a high solid content when it is dispersed in a solvent for modification and preparation of composite materials. Therefore, the CNC suspension must be dried to reduce storage and transportation costs and avoid the growth of bacteria and fungi in the suspension. However, the CNC surface contains a large number of hydroxyl groups, which makes it easy to form hydrogen bonds between or within molecules, resulting in easy aggregation when it is dispersed after drying.

[0004] Therefore, in order to improve the redispersion effect of CNC particles, the surface charge density of CNC can be increased to increase the repulsion between fibers (such as carboxylation, sulfonation, phosphation, quaternization, etc.), or solvent-compatible macromolecules can be introduced on its surface to form steric hindrance and increase interfacial compatibility, thereby meeting the requirement of large-scale application. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a method for preparing cellulose nanocrystals with excellent dispersibility, and the dispersibility of CNC suspension particles is improved by controlling the mass ratio of DMF to CNC.

[0006] The present invention is achieved through the following technical solutions: A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1, mixing the CNC suspension and the polar organic solvent evenly, and then performing ultrasonic treatment to obtain a composite suspension; Step 2, obtaining a cellulose nanocrystal-based composite iridescent film by subjecting the composite suspension to an evaporation-induced self-assembly process; Step 3: dilute the cellulose nanocrystal-based composite iridescent film to form a composite suspension, freeze-dry the composite suspension, and then redisperse the dried product to obtain cellulose nanocrystals with excellent dispersibility.

[0007] Preferably, the polar organic solvent is a DMF solution, a DMSO solution or a NMP solution.

[0008] Preferably, the mass ratio of the CNC suspension to the polar organic solvent is (5-10):1.

[0009] Preferably, the concentration of the composite suspension in step 2 is 1-5 wt %.

[0010] Preferably, the temperature of the composite suspension in step 2 is 20-40°C.

[0011] Preferably, the humidity of the composite suspension in step 2 is 45-65% RH.

[0012] Preferably, the freeze-drying temperature in step 3 is -40°C.

[0013] Preferably, the freeze-drying time in step 3 is 24 hours.

[0014] A cellulose nanocrystal with excellent dispersibility is prepared by adopting the preparation method.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present application provides a method for preparing cellulose nanocrystals with excellent dispersibility, in which CNC is placed in a DMF solution without any other surfactant or chemical modification, which provides a simple strategy for CNC to better combine with other functional substances. By controlling the mass ratio of DMF to CNC, not only the dispersibility of CNC suspension particles can be improved, but also the optical properties of CNC film can be effectively adjusted and a film with uniform apparent color and smooth surface can be obtained. Secondly, since the dried sample will have irreversible hydrogen bonding phenomenon, its redispersibility will deteriorate. In order to improve the redispersibility of CNC particles, the co-solvent strategy of DMF and water is used to reduce the hydrogen bonding between CNC to improve the colloidal stability of the redispersed suspension, which provides a reference for the preparation of CNC-based uniform structural color materials. After testing, this method can effectively improve the aggregation phenomenon of CNC suspension, and the dried product overcomes the problem of easy bacterial growth and strong hygroscopicity of CNC during storage, which is an important step for its functional application in different fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 Atomic force microscope morphology images (AFM) of the cellulose nanocrystal suspension and composite suspension prepared in the present invention.

[0018] Figure 2 Polarized optical microscope (POM) images of the pure cellulose nanocrystal film and composite film prepared in the present invention.

[0019] Figure 3 This is the reflectance spectrum (UV-Vis) of the pure cellulose nanocrystal film and composite film prepared in the present invention.

[0020] Figure 4 This is a scanning electron microscope (SEM) image of the composite membrane prepared in the present invention.

[0021] Figure 5 The ζ-potential measurement value (Zeta potential), dispersion value (PDI) and hygroscopicity test chart (humidity RH) of the dried and redispersed sample prepared in the present invention.

[0022] Figure 6 Bacterial detection diagram of the dried redispersed sample prepared in the present invention. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0024] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0025] The surface of cellulose nanocrystals contains a large number of hydroxyl groups, which makes it easy to form hydrogen bonds between or within molecules, which is also the reason why it is easy to aggregate when it is dispersed after drying. Therefore, in order to improve the redispersion effect of CNC particles, the surface charge density of CNC can be increased to increase the repulsion between fibers (such as carboxylation, sulfonation, phosphorylation, quaternization, etc.), and macromolecules compatible with the solvent can also be introduced on its surface to form steric hindrance and increase interface compatibility.

[0026] A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1, preparation of CNC suspension and composite suspension: Deionized water was used to dilute a CNC suspension with a concentration of 5 wt %, and a polar organic solvent was added to a CNC suspension with a certain concentration, stirred in a magnetic stirrer, and then placed in an ice water bath for ultrasonication to obtain a composite suspension.

[0027] The 5wt% CNC suspension was diluted to a CNC suspension with a concentration of 2-3wt%.

[0028] The concentration of CNC suspension was selected to be 2.2wt%, and the surface of the CNC obtained by sulfuric acid treatment was covered with functional groups such as sulfonic acid groups and hydroxyl groups, and was in the shape of a rod.

[0029] The polar organic solvent is DMF solution, DMSO solution or NMP solution.

[0030] The stirring time of CNC suspension and polar organic solvent was 2 h, and the ultrasonic time was 15 min.

[0031] When the mass ratio CNC:DMF=10:1, the dispersion properties of slightly higher concentration CNC suspension can be significantly improved.

[0032] Step 2, preparation of CNC pure film and mixed film: A certain volume of composite suspension is taken and its concentration, temperature and humidity are controlled to obtain a cellulose nanocrystal-based composite iridescent film through an evaporation-induced self-assembly process.

[0033] Step 3, preparation of redispersed solution and solid powder: The cellulose nanocrystal-based composite iridescent film is placed in a beaker, water is added to obtain a redispersed composite suspension, and the composite suspension is placed in a freeze dryer for drying. The dried samples are then placed in beakers and dispersed to obtain powders, thereby obtaining regulated cellulose nanocrystals.

[0034] The freeze drying temperature was -40°C and the time was 24h. The freeze-dried samples were ground and redispersed separately, and the DMF solution played a positive role in the redispersion of CNC nanoparticles. After being placed for two months, the dried samples had a weak hygroscopic effect and no bacterial contamination was detected.

[0035] This method places CNC in DMF solution without any other surfactants or chemical modifications. The redispersibility is improved after drying. By introducing organic solvents such as N,N-dimethylformamide (DMF), the problems of easy bacterial growth and strong hygroscopicity of CNC during storage are overcome. At the same time, chiral structural color materials with excellent optical properties are obtained, providing an effective means for the construction and functional application of CNC-based composite materials.

[0036] Example 1 A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1: dilute the CNC suspension with a concentration of 5 wt% to a concentration of 2.2 wt% with deionized water, then add DMF solution with a mass ratio of CNC:DMF=10:1, stir in a magnetic stirrer for 2 h, and then place in an ice water bath for ultrasonication for 15 min to obtain a composite suspension; Step 2: 5 mL of the 1 wt % composite suspension was evaporatively induced to self-assemble into a film at a temperature of 25° C. and a humidity of 45% RH. The composite suspension was poured into a circular culture dish with a diameter of 35 mm, and evaporation-induced self-assembly was performed into a cellulose nanocrystal-based composite iridescent film.

[0037] Step 3, dilute the cellulose nanocrystal-based composite iridescent film to form a CNC suspension, obtain a redispersed composite suspension, and place the composite suspension in a freeze dryer for drying at -40°C for 24 hours, place the dried samples in beakers and redisperse them to obtain powders, and obtain the regulated cellulose nanocrystals, marked as, marked as C2.2D.

[0038] Example 2 A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1: Use deionized water to dilute the CNC suspension with a concentration of 5wt% to a concentration of 2.2wt%, then add DMF solution, the mass ratio of CNC:DMF=5:1, stir in a magnetic stirrer for 2h, and then place in an ice water bath for ultrasonication for 15min to obtain a composite suspension.

[0039] Step 2: 5 mL of the composite suspension with a concentration of 1.4 wt % was evaporation-induced to self-assemble into a film at a temperature of 25° C. and a humidity of 45% RH. The composite suspension was poured into a circular culture dish with a diameter of 35 mm, and evaporation-induced self-assembly was performed into a cellulose nanocrystal-based composite iridescent film.

[0040] Step 3, dilute the cellulose nanocrystal-based composite iridescent film to form a CNC suspension, obtain a redispersed composite suspension, and place the composite suspension in a freeze dryer for drying at -40°C for 24 hours, and place the dried samples in beakers and redisperse them to obtain powders, thereby obtaining regulated cellulose nanocrystals.

[0041] Example 3 A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1: Use deionized water to dilute the CNC suspension with a concentration of 5wt% to a concentration of 2.2wt%, then add DMSO solution with a mass ratio of CNC:DMSO=10:1, stir in a magnetic stirrer for 2h, and then place in an ice water bath for ultrasonication for 15min to obtain a composite suspension, marked as C-DMSO.

[0042] Step 2: 5 mL of the composite suspension with a concentration of 1.8 wt % was evaporation-induced to self-assemble into a film at a temperature of 25° C. and a humidity of 45% RH. The composite suspension was poured into a circular culture dish with a diameter of 35 mm, and evaporation-induced self-assembly was performed into a cellulose nanocrystal-based composite iridescent film.

[0043] Step 3, the composite suspension formed by diluting the cellulose nanocrystal-based composite iridescent film is placed in a freeze dryer and dried at a drying temperature of -40°C for 24 hours. The dried samples are placed in beakers and dispersed to obtain powders, thereby obtaining regulated cellulose nanocrystals, which are marked as C-DMSO.

[0044] Example 4 A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1: Use deionized water to dilute the CNC suspension with a concentration of 5wt% to a concentration of 2.2wt%, then add NMP solution, the mass ratio of CNC:NMP=10:1, stir in a magnetic stirrer for 2h, and then place in an ice water bath for ultrasonication for 15min to obtain a composite suspension.

[0045] Step 2: 5 mL of the composite suspension with a concentration of 2.2 wt % was evaporation-induced to self-assemble into a film at a temperature of 25° C. and a humidity of 45% RH. The composite suspension was poured into a circular culture dish with a diameter of 35 mm, and evaporation-induced self-assembly was performed into a cellulose nanocrystal-based composite iridescent film.

[0046] Step 3, the composite suspension formed by diluting the cellulose nanocrystal-based composite iridescent film is placed in a freeze dryer and dried at a drying temperature of -40°C for 24 hours. The dried samples are placed in beakers and dispersed to obtain powders, thereby obtaining regulated cellulose nanocrystals, which are marked as C-NMP.

[0047] Example 5 A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1: Use deionized water to dilute the CNC suspension with a concentration of 5wt% to a concentration of 2.2wt%, then add NMP solution, the mass ratio of CNC:NMP=10:1, stir in a magnetic stirrer for 2h, and then place in an ice water bath for ultrasonication for 15min to obtain a composite suspension.

[0048] Step 2: 5 mL of the 3 wt % composite suspension was induced to self-assemble into a film by evaporation at a temperature of 25° C. and a humidity of 45% RH. The composite suspension was poured into a circular culture dish with a diameter of 35 mm, and evaporation-induced self-assembly was performed under ambient conditions to form a cellulose nanocrystal-based composite iridescent film.

[0049] Step 3, the composite suspension formed by diluting the cellulose nanocrystal-based composite iridescent film is placed in a freeze dryer for drying at a temperature of -40°C for 24 hours, the dried samples are placed in beakers and dispersed to obtain powders, thereby obtaining regulated cellulose nanocrystals.

[0050] Example 6 A method for preparing cellulose nanocrystals with excellent dispersibility comprises the following steps: Step 1: Use deionized water to dilute the CNC suspension with a concentration of 5wt% to a concentration of 1wt%, then add DMF solution, the mass ratio of CNC:DMF=10:1, stir in a magnetic stirrer for 2h, and then place in an ice water bath for ultrasonication for 15min to obtain a composite suspension.

[0051] Step 2: 5 mL of the 5 wt % composite suspension was evaporatively induced to self-assemble into a film at a temperature of 25° C. and a humidity of 45% RH. The composite suspension was poured into a circular culture dish with a diameter of 35 mm, and evaporation-induced self-assembly was performed into a cellulose nanocrystal-based composite iridescent film.

[0052] Step 3, dilute the cellulose nanocrystal-based composite iridescent film to form a CNC suspension, obtain a redispersed composite suspension, and place the composite suspension in a freeze dryer for drying at -40°C for 24 hours, and place the dried samples in beakers and redisperse them to obtain powders, thereby obtaining regulated cellulose nanocrystals.

[0053] The following is an experimental analysis of the regulated cellulose nanocrystals prepared in Examples 1-6, as follows: The CNC suspension with a concentration of 2.2wt% is denoted as C2.2. Figure 1 The AFM images of the microscopic morphology of CNC (C2.2) and CNC / DMF composite suspension (C2.2D) at different magnifications clearly show that the CNC nanoparticles are rod-shaped (i.e., needle-shaped). When the concentration of the CNC suspension is 2.2wt%, some aggregation occurs, forming partially overlapping and aggregated nanoparticles. When the concentration continues to increase to 3-5wt%, serious aggregation occurs, so it is necessary to effectively adjust its dispersion.

[0054] Figure 2 The properties of the CNC film solid phase were characterized by POM. The color of the films with different concentrations was uniform and bright blue, indicating that the long-range orientation of the CNC domain was strong. Among them, the C2.2 film had a more saturated structural color and no coffee ring phenomenon.

[0055] Figure 2 The C2.2D cellulose nanocrystal-based composite iridescent film was characterized by POM, which showed obvious birefringence and a relatively uniform bright blue pattern. It is worth noting that the photonic crystals in the pure CNC film converged to show a large micro-color domain, resulting in an uneven distribution of colors. However, after the introduction of DMF, the blue photonic crystals gathered in smaller micro-color domains and were evenly distributed in the composite film. The color of the C2.2D cellulose nanocrystal-based composite iridescent film is more uniform and can be clearly observed by the naked eye.

[0056] Figure 2 The C-DMSO and C-NMP films were characterized by POM. Compared with the C2.2D film, the C-DMSO cellulose nanocrystal-based composite iridescent film and the C-NMP cellulose nanocrystal-based composite iridescent film also showed obvious birefringence, but neither of them showed a single color pattern. Not only did the coffee ring phenomenon appear, but the surface of the cellulose nanocrystal-based composite iridescent film was uneven and wrinkled.

[0057] DMF interacts with CNC through hydrogen bonds. Figure 3It can be seen that compared with the cellulose nanocrystal-based composite iridescent film with a mass ratio of CNC:DMF=5:1, the cellulose nanocrystal-based composite iridescent film with a mass ratio of CNC:DMF=10:1 has a higher reflection peak, indicating that its optical properties are better, and also indicating that an appropriate amount of DMF can improve the optical properties of the film.

[0058] Whether the color of cellulose nanocrystal-based composite iridescent films is uniform is determined by the order of the pitch. Figure 4 The cross section of the cellulose nanocrystal-based composite iridescent film can be observed by scanning electron microscopy. After adding DMF, the cross section of the cellulose nanocrystal-based composite iridescent film also clearly presents a regular layered spiral structure and a consistent chiral nematic order, which is the reason why the cellulose nanocrystal-based composite iridescent film has structural color. This shows that the addition of an appropriate amount of DMF will not hinder the occurrence of CNC self-assembly behavior, and the formed spiral structure and arrangement direction are not significantly affected.

[0059] Figure 5 (a) It can be seen that the ζ-potential values ​​of R-C2.2 and R-C2.2D samples after redispersion treatment are -17.9 mV and -35.6 mV, respectively, and the PDI dispersion index is 0.306 and 0.270, respectively. It can be seen that compared with the introduction of DMF solution, the absolute value of the ζ-potential value of the sample without DMF solution is smaller, which indicates that DMF solution plays a positive role in the redispersion effect of CNC nanoparticles. At the same time, both have lower PDI dispersion index values, indicating that they can still be redispersed after freeze-drying.

[0060] The redispersion of CNC suspension was labeled as R-C2.2, and the redispersion of C2.2D was labeled as R-C2.2D. After the R-C2.2 and R-C2.2D samples were stored for a period of time, R-C2.2 showed signs of severe aggregation, which indicated that the redispersion of the suspension was incomplete, while the latter had a slight floating phenomenon, indicating that its dispersion was relatively complete. This result was attributed to the formation of hydrogen bonds between DMF and water, which effectively prevented the formation of hydrogen bonds between CNCs, thereby reducing the hydrogen bonds between CNCs and improving the redispersion.

[0061] Figure 5 (b) It can be seen that the dried samples DG-C2, DG-C2.2D, and DG-C5 have a weak moisture absorption effect after being placed for two months, which may have certain limitations on their application. Figure 6 It can be seen that no bacterial contamination was detected in the samples.

[0062] The present application can improve the dispersibility of CNC suspension particles by controlling the mass ratio of DMF to CNC, and can also effectively adjust the optical properties of the CNC film, and the obtained film has uniform apparent color and a smooth surface. Since the dried sample will have irreversible hydrogen bonding, which will lead to poor redispersibility, in order to improve the redispersibility of CNC particles, the co-solvent strategy of DMF and water is used to reduce the hydrogen bonding between CNCs, thereby improving the colloidal stability of the redispersed suspension, which is beneficial to the preservation and storage of the sample.

[0063] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing cellulose nanocrystals with excellent dispersibility, characterized in that: The following steps are involved: Step 1, mixing the CNC suspension and the polar organic solvent evenly, and then performing ultrasonic treatment to obtain a composite suspension; Step 2, obtaining a cellulose nanocrystal-based composite iridescent film by subjecting the composite suspension to an evaporation-induced self-assembly process; Step 3: dilute the cellulose nanocrystal-based composite iridescent film to form a composite suspension, freeze-dry the composite suspension, and then redisperse the dried product to obtain cellulose nanocrystals with excellent dispersibility.

2. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The polar organic solvent is DMF solution, DMSO solution or NMP solution.

3. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The mass ratio of the CNC suspension to the polar organic solvent is (5-10):

1.

4. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The concentration of the composite suspension in step 2 is 1-5 wt %.

5. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The temperature of the composite suspension in step 2 is 20-40°C.

6. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The humidity of the composite suspension in step 2 is 45-65% RH.

7. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The freeze-drying temperature in step 3 is -40°C.

8. The method for preparing cellulose nanocrystals with excellent dispersibility according to claim 1, characterized in that: The freeze drying time in step 3 is 24h.

9. A cellulose nanocrystal with excellent dispersibility, characterized in that: The cellulose nanocrystals are prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Self-healing cellulose nanocrystalline photonic membrane and preparation method thereof

    CN116751396A

  • Redispersible nanocellulose, and method of manufacturing the same

    KR1020180120355A